The Search for the Four-electron Reduced Intermediate in the Cytochrome C Nitrite Reductase (CCNIR) - Catalyzed Reduction of Nitrite - (:unkn) unknown (My University, 2023)
Although there are many nitrogen species in the nitrogen cycle, nitrite occupies a centralrole. Nitrite can either reduce to ammonium or dinitrogen or oxidize to nitrate. Ammonium and nitrate can be found in the environment; however, problems arise when the accumulation of these nitrogen species leads to eutrophication in aquatic environments. High ammonium or nitrate levels in lakes or other bodies of water can lead to the overgrowth of algae, which causes the blockage of sunlight to different species below the water surface. Imbalance in the ecosystem is a serious environmental issue that can be addressed by further studying and understanding the nitrogen cycle. Cytochrome c Nitrite Reductase (ccNiR) is a complex multi-heme respiratory enzyme, found in the aquatic bacteria Shewanella oneidensis, that catalyzes the reduction of nitrite to ammonium. Earlier in vitro studies had used the strong reductant methyl viologen monocation radical (MVred) to study the reaction, but under these conditions, no intermediates accumulate, which leaves the mechanistic steps of the catalysis uncharted. In this study, ccNiR-mediated nitrite reduction was effected by a variety of weak reductants in place of MVred. Assays for hydroxylamine and ammonium formation showed that ammonium was still the only significant product under these conditions. However, intermediate species in which partially reduced nitrogenous moieties were bound at the ccNiR active site were now detectable. The kinetics of intermediate and ammonium formation were monitored by conventional and stopped-flow UV-Visible Spectroscopy. The results presented herein pave the way to further characterizing the catalytic intermediates using electron paramagnetic resonance spectroscopy and time resolved X-ray crystallography. To that end, preliminary crystallographic results collected at the European X-Ray free-electron laser facility are also presented.